2003
DOI: 10.1074/jbc.m302717200
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Mouse Hematopoietic Progenitors by Specific Retroviral Infection

Abstract: Previous studies have identified an enhancer 3 of the scl gene that can direct transgene expression to hematopoietic progenitors and stem cells. Here we use this enhancer to restrict expression of the avian leukosis virus receptor, TVA, to hematopoietic stem cells and progenitors in bone marrow and fetal liver and demonstrate that retroviral infection can be used to specifically introduce exogenous sequences. We show that a majority of CFU-S 12 multipotential progenitor cells can be transduced in vitro. Unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Using reporter genes, we have shown that the +19 enhancer directs expression to HSCs in transgenic mice. The Tal1 enhancer has also been used to generate mouse models for inducible transgene expression, retroviral gene transfer, and Cre-mediated recombination as well as the development of acute myeloid leukemia mouse models (Murphy et al 2003;Eguchi et al 2005;Gothert et al 2005;Koschmieder et al 2005). At the molecular level, activity of the +19 element critically depends on binding sites for the Ets and GATA families of transcription factors and this combination of transcription factors constitutes a regulatory code employed by several other enhancers Pimanda et al 2006Pimanda et al , 2007aChan et al 2007;Landry et al 2008) that display similar expression patterns in transgenic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Using reporter genes, we have shown that the +19 enhancer directs expression to HSCs in transgenic mice. The Tal1 enhancer has also been used to generate mouse models for inducible transgene expression, retroviral gene transfer, and Cre-mediated recombination as well as the development of acute myeloid leukemia mouse models (Murphy et al 2003;Eguchi et al 2005;Gothert et al 2005;Koschmieder et al 2005). At the molecular level, activity of the +19 element critically depends on binding sites for the Ets and GATA families of transcription factors and this combination of transcription factors constitutes a regulatory code employed by several other enhancers Pimanda et al 2006Pimanda et al , 2007aChan et al 2007;Landry et al 2008) that display similar expression patterns in transgenic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cell type-specific activity of this cassette outside the hematopoietic system has not been investigated [58]. The small size and robust in vivo activity of the SCL +18/19 enhancer has led several groups to use it as a way of targeting expression to HSCs [19][20][21][22][23]59]. Therefore, comprehensive analysis of the in vivo activity of the SCL +18/19 enhancer within and outside the hematopoietic system not only provides further insights into transcriptional regulation of SCL but will be vital to interpret current and future mouse models generated using this powerful regulatory element.…”
Section: Discussionmentioning
confidence: 99%
“…The +18/19 enhancer was originally characterized as a 5,245-bp fragment. This fragment has been used to direct HSC expression of several proteins, including SCL itself [19], Cre recombinase [20], tetracycline transactivator [21], the TVA avian retroviral receptor protein [22], and oncogenic fusion proteins [23]. Interpretation of these and future studies using this experimental approach will require detailed knowledge of the precise cell types targeted.…”
Section: Introductionmentioning
confidence: 99%
“…The transgenic SCL-TVA/C57BL6 mice used in these studies have been described previously (19). SCL-TVA mice carry a 9-kb transgene (p6E5/TVA/3 ¶E) in which a 950-bp TVA cDNA was cloned downstream of p6E5, a 2.8-kb murine scl promoter element, and upstream of the 5.5-kb murine 3 ¶ enhancer from the murine scl locus (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This made it possible to induce cell type -specific neoplasms in TVA transgenic mice by infection with recombinant RCAS viruses (15 -18). Murphy et al have reported previously on the creation of transgenic mice in which the TVA receptor of avian leukosis virus was under the control of the SCL promoter and the SCL +19 enhancer (19). This SCL-TVA/RCAS system was used to deliver genes to HSC using recombinant RCAS viruses in vitro.…”
mentioning
confidence: 99%